STRATEGI KOMUNIKASI PEMASARAN TATV DALAM UPAYA MEMPERKENALKAN PRODUK Chocomania - Setyawan, Agustinus (Transformasi, 2015)
Modern marketing is not just oriented in a way to develop a good product, and has appeal to invite public attention. In this study, researchers used the title "Marketing Communication Strategy In Effort Introducing TATV Chocomania Products". This study uses the theory Terance A and Don E. Schultz on marketing communications strategies. The method is performed by penilitian descriptive qualitative, which attempt to explain a problem or situation and activities as they are. Marketing Communications strategy used consists of several activities, namely by identifying target audiences to determine the target audience, specialization event and the event made activities preferred activities involving mass target audience. ................................. Keywords: Marketing Communication Strategy, tv media, introducing